Array - Nurfitri, Ika Nisa (Paradigma, 2021)
Abstract Indonesia's population growth from year to year is increasing. BPS data for 2015 shows that the total population of Indonesia in 2015 was 238,518,000. In the 2015 BPS data report, it is predicted that there will be an increase in the population in 2020. The government established the Population and Family Planning Agency. The BKKBN has a family planning program that aims to delay, spacing, and regulate pregnancy spacing. One of the existing family planning methods is tubectomy. Tubectomy or what is commonly called MOW is one of the long-term family planning methods. Tubectomy KB method is performed by surgery. Based on data on active family planning participants in 2018 in East Java, especially users of the tubectomy family planning method reached 287,444 in fertile age couples in several cities and districts. Jombang Regency which is known as the city of santri is in 6th position with the highest number of tubectomy family planning participants. The purpose of this study is to identify the sources of information, perspectives, factors, processes, and rationality of decision making for reproductive age couples using tubectomy family planning in the santri community in Jombang Regency. Researchers used Max Weber's rationality action theory to be used as a knife of analysis in this study. The approach used is grounded theory. The grounded theory approach consists of three stages, namely open coding, axial coding, and selective coding. The results of this study indicate that there are four types of Max Weber's rationality actions when making decisions on using tubectomy family planning for reproductive age couples who come from the santri community in Jombang Regency. Keywords: Tubectomy Family Planning, Santri Society, Fertile Age Couples The Rationality of Decision Making